Circulating Factors Induced by Caloric Restriction in the Nonhuman Primate Macaca Mulatta Activate Angiogenic Processes in Endothelial Cells - Csiszar, Anna (Oxford University Press, 2013)
Moderate caloric restriction (CR) without malnutrition increases healthspan in virtually every species studied, including nonhuman primates. In mice, CR exerts significant microvascular protective effects resulting in increased microvascular density in the heart and the brain, which likely contribute to enhanced tolerance to ischemia and improved cardiac performance and cognitive function. Yet, the underlying mechanisms by which CR confer microvascular protection remain elusive. To test the hypothesis that circulating factors triggered by CR regulate endothelial angiogenic capacity, we treated cultured human endothelial cells with sera derived from Macaca mulatta on long-term (over 10 years) CR. Cells treated with sera derived from ad-libitum-fed control monkeys served as controls. We found that factors present in CR sera upregulate vascular endothelial growth factor (VEGF) signaling and stimulate angiogenic processes, including endothelial cell proliferation and formation of capillary-like structures. Treatment with CR sera also tended to increase cellular migration (measured by a wound-healing assay using electric cell–substrate impedance sensing [ECIS] technology) and adhesion to collagen. Collectively, we find that circulating factors induced by CR promote endothelial angiogenic processes, suggesting that increased angiogenesis may be a potential mechanism by which CR improves cardiac function and prevents vascular cognitive impairment.